Bible through the lens of trauma - Boase, Elizabeth, 1963-; Frechette, Christopher G. (Atlanta : SBL Press, 2016)
"In recent years there has been a surge of interest in trauma, trauma theory, and its application to the biblical text. This collection of essays explores the usefulness of using trauma theory as a lens through which to read the biblical texts. Each of the essays explores the concept of how trauma might be defined and applied in biblical studies. Using a range of different but intersection theories of trauma, the essays reflect on the value of trauma studies for offering new insights into the biblical text. Including contributions from biblical scholars, as well as systematic and pastoral theologians, this book provides a timely critical reflection on this emerging discussion"--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Bible. -- Criticism, interpretation, etc; Psychic trauma -- Biblical teaching; BIBLES / General; RELIGION / Biblical Reference / General; RELIGION / Biblical Reference / Handbooks; Electronic books